The Effect of Fear of Missing Out on Phubbing Behavior: Self-Control as a Moderating Variable among Indonesian Science Students - Prakoso, Emannuel Realeno Isyaalma Wahyu; Ayriza, Yulia (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: The purpose of this study is to examine the effect of Fear of Missing Out (FOMO) on phubbing behavior among Indonesian science students and to investigate whether self-control plays a moderating role in the relationship between FOMO and phubbing behavior. Methodology: This study uses a quantitative correlational approach with a survey. Data were collected from 402 Indonesian science students aged 19–38 years across 28 regions. The instruments included the Fear of Missing Out Scale, the Phubbing Behavior Scale, and the Self-Control Scale. Data were analyzed using moderation analysis with statistical software. Main Findings: The results showed that Fear of Missing Out (FOMO) had a positive and significant effect on phubbing behavior (β = 0.655, p = 0.001). Self-control also demonstrated a significant direct effect on phubbing behavior (β = 0.279, p = 0.005). However, the interaction between FOMO and self-control was not statistically significant (β = −0.005, p = 0.098), indicating that self-control did not moderate the relationship between FOMO and phubbing behavior among students. Novelty/Originality of this study: This study contributes novel empirical evidence by testing self-control as a moderator in the relationship between FOMO and phubbing behavior in a large and diverse Indonesian science student sample. The findings highlight the limitation of trait-based self-control measures and suggest the need to conceptualize self-control as a situational or media-related state.